A protective layer of lithium metal and a construction method thereof, lithium metal and application thereof
By constructing a protective layer composed of perfluoropolyether oil and hydrophobic porous polymer on the surface of lithium metal, the safety problems caused by the restricted application of lithium metal negative electrodes in anhydrous and oxygen-free environments and the growth of lithium dendrites are solved, and the flexible protection of lithium metal and the improvement of battery circulation performance are achieved.
Patent Information
- Application Number
- CN202411755998.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The application of lithium metal negative electrodes in high-cost anhydrous and oxygen-free manufacturing environments is limited, and the uncontrollable growth of lithium dendrites leads to safety problems. The existing solid-state protective film has a large thickness and is not flexible, which limits its application range.
A hydrophobic porous polymer coating is used as the protective layer of lithium metal. The coating consists of perfluoropolyether oil and hydrophobic porous polymer. It has flexibility and thickness, can co-deform with lithium metal, and conduct lithium ions through the holes without electrons.
Effectively isolate oxygen and moisture in the air, protect lithium metal, maintain its flexibility and coilability, delay the growth and short circuit of lithium dendrites, and improve the circulating performance of the battery.
Smart Images

Figure CN119252863B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a lithium metal protective layer and a construction method thereof, lithium metal and applications thereof. Background Art
[0002] Lithium metal anode is considered the "holy grail" of anode materials due to its high theoretical specific capacity (3860mAh / g) and low redox potential (-3.04V compared to standard hydrogen electrode). Studies have shown that uneven distribution of ion flux on the surface of lithium metal, volume changes, unstable SEI film, etc. can lead to uncontrollable growth of lithium dendrites, resulting in serious safety problems. More importantly, the industrial-scale application of metal lithium anode is limited by the high-cost anhydrous and oxygen-free manufacturing environment, which requires avoiding any exposure to humid air, otherwise the cycle performance and life will be significantly reduced or even fail. This strict anhydrous and oxygen-free assembly environment poses a challenge to its practical widespread application.
[0003] Chinese patent document CN 114204102 A discloses a waterproof, air-proof, dendrite-suppressing all-solid-state lithium metal protective film and its construction strategy. The prepared all-solid-state lithium metal protective film has a layered composite structure, with a polymer interface layer, a solid electrolyte layer and a hydrophobic layer to achieve the stability of the lithium negative electrode in water and air, and electrochemical stability. This preparation method requires high-temperature sintering to attach a solid ceramic electrolyte ceramic sheet to the polymer interface. The protective film thus prepared is solid, with a solid ceramic electrolyte ceramic sheet attached to it. It is not only thick, but also has no flexibility. It cannot be deformed after being made, and its application range is limited. Summary of the invention
[0004] The purpose of the present invention is to provide a lithium metal protective layer which is flexible, thin and has a simple preparation method; and which can effectively protect lithium metal from contact with air and water and can be applied to lithium strips to be rolled, lithium ion battery negative electrodes, etc.
[0005] The technical solution of the present invention is:
[0006] A protective layer for lithium metal comprises a hydrophobic porous polymer coating adhered to the lithium metal, wherein the holes and the adhered surface of the hydrophobic porous polymer coating contain perfluoropolyether oil.
[0007] The lithium metal protective layer of the present invention has perfluoropolyether oil in the pores and surface of the hydrophobic porous polymer coating, and the hydrophobic porous polymer coating is attached to the surface of the lithium metal. The perfluoropolyether oil and the hydrophobic porous polymer coating separate the lithium metal from the outside air, thereby preventing oxygen and moisture in the air from reacting with the lithium. The porous polymer coating is flexible and can be deformed together with the lithium metal without breaking. Therefore, the lithium metal protective layer of the present invention is attached to the lithium metal and does not affect the winding of the lithium metal. In particular, when such a lithium ribbon is used as the negative electrode of a lithium ion battery, the hydrophobic porous polymer coating itself has the property of not conducting electrons; the perfluoropolyether oil in its pores has the property of conducting lithium ions. Therefore, the lithium metal protective layer of the present invention can conduct lithium ions through the pores of the hydrophobic porous polymer without conducting electrons. Such a protective layer is on the outer surface of the lithium material, and the lithium material can be directly used as a lithium negative electrode substrate without removing the protective layer. Furthermore, even if conditions for the generation and growth of lithium dendrites occur during the battery charge and discharge process, since lithium ions are conducted in the porous polymer according to specific channels in such a lithium metal protective layer, the lithium deposition and the growth direction of lithium dendrites are distorted by the guidance of the hole channels, thereby delaying the occurrence of short circuits. In addition, the protective film of the present invention moderately isolates lithium metal from the electrolyte, alleviates the reaction consumption of the electrolyte on the surface of the lithium metal during the battery charge and discharge cycle, and improves the cycle performance of the battery.
[0008] Preferably, the hydrophobic porous polymer coating is a hydrophobic porous polypropylene layer.
[0009] Preferably, the hydrophobic porous polypropylene layer has a thickness of 0.5 to 30 μm.
[0010] Preferably, the hydrophobic porous polypropylene layer has a thickness of 10 to 20 μm. The lithium metal protective layer of this thickness can replace the diaphragm, and the diaphragm does not need to be assembled when making the battery.
[0011] Preferably, the perfluoropolyether oil is CF3CF2CF2O(CF2CF2CF2O)mCF2CF3, CF3CF2CF2O(CF(CF3)CF2O) m At least one of CF(CF3)COF, CF3O ((CF2)3O)m(CF2O)nCF3 and CF3O (CF2CF2O)m(CF2O)nCF3, with a number average molecular weight of 1000 to 3000. Perfluoropolyether oil with such a molecular weight has a moderate viscosity, which is beneficial to the migration of lithium ions within the operating temperature range of the battery. In addition, it has a low surface tension. When the electrolyte is injected into the battery, part of the perfluoropolyether oil exchanges positions with the electrolyte and enters the electrolyte, which can enhance the wetting performance of the electrolyte; at the same time, the presence of fluorine can also improve the heat resistance of the electrolyte, thereby making the battery safer.
[0012] The present invention also provides a method for constructing the protective layer of the lithium metal, comprising the following steps:
[0013] Step 1: Add a mixture of a polymer, a good solvent for the polymer and a poor solvent in a volume ratio of 10:1-5 into a container and stir until a homogeneous solution is formed, and apply the mixture on a flat surface of a substrate; let it stand at 10-40°C for 3-12 hours under a vacuum degree of ≤-90 kPa; dry it at 20-25°C under normal pressure to form a film, put it in a vacuum drying oven at 60-80°C and dry it for 22-25 hours to obtain a porous polypropylene-coated polytetrafluoroethylene; peel it off to obtain a hydrophobic porous polymer film;
[0014] The substrate may be made of polytetrafluoroethylene, or other materials with lower surface energy may be selected to facilitate demolding.
[0015] Step 2: After coating the surface of the hydrophobic porous polymer membrane with perfluoropolyether oil, the coated surface is attached to the surface of the lithium material.
[0016] In step 1, after the polymer forms a homogeneous solution in its good solvent and poor solvent and is coated on the surface of the substrate, under the conditions of vacuum degree ≤-90kPa and 10-40°C, the polymer is phase separated and enriched between its good solvent and poor solvent. After standing for 3-12 hours, the good solvent and the poor solvent evaporate to cause the polymer to crystallize, and the crystals form a polymer porous structure under the rapid volatilization of the good solvent and the poor solvent. After the solvent is naturally volatilized at 20-25°C, the porous structure matures and sets, and a hydrophobic porous polymer membrane is obtained. After the surface of the hydrophobic porous polymer membrane is coated with perfluoropolyether oil in step 2, since both the hydrophobic porous polymer and the perfluoropolyether oil are lipophilic substances, and the low surface tension of the perfluoropolyether oil makes it have strong permeability and spreadability, the perfluoropolyether oil enters the holes of the porous structure through capillary action and is embedded with the hydrophobic porous polymer membrane; when the coated surface of the hydrophobic porous polymer membrane is close to the surface of the lithium material, under the action of atmospheric pressure, the perfluoropolyether oil quickly spreads between the hydrophobic porous polymer membrane and the lithium material, and the two are pulled close and fitted together, thereby isolating the lithium material from the air and preventing corrosion by water and oxygen in the air.
[0017] Preferably, the polymer is isotactic polypropylene with a number average molecular weight of 200,000 to 300,000; the good solvent is at least one of xylene, toluene, benzene and decalin; and the poor solvent is at least one of butanone, ethanol, methanol, n-butanol and n-propanol.
[0018] Preferably, the coating in step 2 is performed by dipping, brushing or spraying.
[0019] The present invention also provides a lithium metal, comprising the above metal lithium protective layer. The lithium metal of the present invention has the above metal lithium protective layer, thus reducing the requirements for the operating environment and reducing the processing, transportation and storage costs.
[0020] The present invention also provides an application of the above-mentioned lithium metal, which is used as a negative electrode of a lithium battery or a lithium ion battery. The lithium metal of the present invention has the above-mentioned metal lithium protective layer, the perfluoropolyether oil in the protective layer has lithium ion conductivity, and the polymer itself is insulating. Therefore, when the lithium metal with the protective layer of the present invention is used as a negative electrode of a battery, the protective layer has electronic insulation and lithium ion conductivity, and can be used directly without removing the protective layer.
[0021] The beneficial effects of the present invention are:
[0022] The method for constructing the protective layer of lithium metal of the present invention is to prepare a hydrophobic porous polymer film, coat the hydrophobic porous polymer film with perfluoropolyether oil, and then adhere it to the surface of a lithium material to obtain the protective layer of lithium metal. The protective layer isolates oxygen and moisture in the air to protect the lithium metal, is flexible, and can be rolled together with the lithium metal without breaking; the hydrophobic porous polymer coating itself has electronic insulation, and the perfluoropolyether oil in the pores conducts lithium ions but not electrons. The lithium belt of the present invention can be directly used as a negative electrode substrate without removing the protective layer, and is easy to use; and the protective layer alleviates the reaction consumption of the electrolyte on the electrode surface during the battery cycle, thereby improving the battery cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the SEM image of the hydrophobic porous polypropylene membrane prepared in Example 1.
[0024] Figure 2 This is a moving picture of a 5μL water droplet falling on a metallic lithium ribbon with a lithium metal protective layer.
[0025] Figure 3 The contact angle of a water drop on a metallic lithium strip with a lithium metal protective layer measured by a fully automatic video micro contact angle meter. DETAILED DESCRIPTION
[0026] The present invention is described in detail below in conjunction with the examples. The lithium ribbon used below is produced by Tianjin Zhongneng Lithium Industry Co., Ltd., has a thickness of 100-300 μm, and is operated after being purged with argon gas.
[0027] Example 1
[0028] Constructing a protective layer on the surface of the lithium metal strip is as follows:
[0029] Step 1: mix toluene and butanone in a volume ratio of 9:1 to prepare a mixed solution, add isotactic polypropylene with a number average molecular weight of 200,000 at a concentration of 20 mg / mL, and stir at 130°C until a homogeneous solution is formed; apply it on the surface of a flat plate made of polytetrafluoroethylene; let it stand at 30°C for 6 hours under a vacuum condition of -95 kPa; dry it at 20-25°C under normal pressure to form a film, put it in a vacuum drying oven at 60°C and dry it for 24 hours to obtain porous polypropylene-coated polytetrafluoroethylene; peel it off from the polytetrafluoroethylene substrate to obtain a hydrophobic porous polypropylene film with a thickness of 15 μm.
[0030] Figure 1 : is a SEM image of the hydrophobic porous polypropylene membrane prepared in this embodiment. Figure 1 It can be seen that it has many intersecting hole structures.
[0031] Step 2: dip-coat the hydrophobic porous polypropylene membrane on both sides with perfluoropolyether oil CF3CF2CF2O(CF2CF2CF2O)mCF2CF3, where the number average molecular weight of the perfluoropolyether oil is 2000; and then attach it to the surface of the lithium strip in an argon atmosphere to produce a metal lithium strip with a lithium metal protective layer.
[0032] Using a disposable dropper, water drops were dropped on the surface of the metal lithium strip with the lithium metal protective layer prepared above, and the movement of the water drops on the surface was filmed with a high-speed camera under a double-branch cold light source MSHOT H-150. Figure 2 The motion picture obtained by continuous shooting is Figure 2 It can be seen that the water drop falls on the surface until it moves on the surface without wetting at all, and the water drop slides in a spherical shape.
[0033] A 5 μL water droplet was dropped on the surface of the metal lithium strip with the lithium metal protective layer prepared in this embodiment, and the contact angle of the water droplet on the lithium strip surface was measured using a fully automatic video microscopic contact angle measuring instrument of model OCA40Micro. The measured WCA was 160°, indicating that the lithium metal protective layer is not wetted by water.
[0034] Example 2
[0035] Constructing a protective layer on the surface of the lithium metal strip is as follows:
[0036] Step 1: xylene and ethanol are mixed in a volume ratio of 10:1 to prepare a mixed solution, isotactic polypropylene with a number average molecular weight of 300,000 is added at a concentration of 20 mg / mL, and stirred at 130°C until a homogeneous solution is formed; the solution is applied on the surface of a flat plate made of polytetrafluoroethylene; the solution is allowed to stand at 30°C for 3 hours under a vacuum degree of -95 kPa; the solution is dried at 20 to 25°C under normal pressure to form a film, and the film is dried in a vacuum drying oven at 80°C for 23 hours to obtain porous polypropylene-coated polytetrafluoroethylene; and a hydrophobic porous polypropylene film with a thickness of 10 μm is obtained by peeling the film off from the polytetrafluoroethylene substrate.
[0037] Step 2: Spray perfluoropolyether oil CF3CF2CF2O (CF(CF3)CF2O) on both sides of the hydrophobic porous polypropylene membrane m CF(CF3)COF, perfluoropolyether oil with a number average molecular weight of 2000, was then bonded to the surface of the lithium strip in an argon atmosphere.
[0038] Example 3
[0039] Step 1, benzene and n-propanol are mixed in a volume ratio of 8:1 to prepare a mixed solution, isotactic polypropylene with a number average molecular weight of 200000 is added at a concentration of 20 mg / mL, and stirred at 130°C until a homogeneous solution is formed; the solution is applied on the surface of a flat plate made of polytetrafluoroethylene material; the solution is allowed to stand at 10°C for 12 hours under a vacuum condition of -95 kPa; the solution is dried at 20-25°C under normal pressure to form a film, and the film is dried in a vacuum drying oven at 70°C for 22 hours to obtain porous polypropylene-coated polytetrafluoroethylene; a hydrophobic porous polypropylene film with a thickness of 30 μm is obtained by peeling the film off from the polytetrafluoroethylene substrate.
[0040] Step 2: Spray perfluoropolyether oil CF3O ((CF2)3O)m(CF2O)nCF3 on both sides of the hydrophobic porous polypropylene membrane, where the number average molecular weight of the perfluoropolyether oil is 2000, and then adhere it to the surface of the lithium strip in an argon atmosphere.
[0041] Example 4
[0042] Step 1, decalin and n-butanol are mixed in a volume ratio of 2:1 to prepare a mixed solution, isotactic polypropylene with a number average molecular weight of 200,000 is added at a concentration of 20 mg / mL, and stirred at 130°C until a homogeneous solution is formed; the solution is applied on the surface of a flat plate made of polytetrafluoroethylene; the solution is allowed to stand at 40°C for 10 hours under a vacuum condition of -95 kPa; the solution is dried at 20-25°C at normal pressure to form a film, and the film is dried at 60°C in a vacuum drying oven for 25 hours to obtain porous polypropylene-coated polytetrafluoroethylene; and the film is peeled off to obtain a hydrophobic porous polypropylene film with a thickness of 0.5 μm.
[0043] Step 2: Double dip coating the hydrophobic porous polypropylene membrane with perfluoropolyether oil CF3O (CF2CF2O)m(CF2O)nCF3, where the number average molecular weight of the perfluoropolyether oil is 1000, and then laminating it on the surface of the lithium strip in an argon atmosphere.
[0044] Example 5
[0045] Step 1, xylene and methanol are mixed in a volume ratio of 5:1 to prepare a mixed solution, isotactic polypropylene with a number average molecular weight of 300000 is added at a concentration of 20 mg / mL, and stirred at 130°C until a homogeneous solution is formed; apply it on the surface of a flat plate made of polytetrafluoroethylene; let it stand at 20°C for 8 hours under a vacuum condition of -95 kPa; dry it at 20-25°C at normal pressure to form a film, put it in a vacuum drying oven at 80°C and dry it for 24 to obtain porous polypropylene-coated polytetrafluoroethylene; peel it off to obtain a hydrophobic porous polypropylene film with a thickness of 0.5 μm.
[0046] Step 2: Coat both sides of the hydrophobic porous polypropylene membrane with perfluoropolyether oil CF3CF2CF2O(CF2CF2CF2O)mCF2CF3, where the number average molecular weight of the perfluoropolyether oil is 3000, and then attach the membrane to the surface of the lithium strip in an argon atmosphere.
[0047] Comparative Example 1
[0048] The lithium ribbon in Example 1 was used directly without forming a protective layer.
[0049] Performance Test:
[0050] 1. Protection performance test
[0051] In an argon atmosphere, the lithium metal ribbons with lithium metal protective layers prepared in Examples 1 to 5 and the lithium ribbon without a protective layer prepared in Comparative Example 1 were placed together at a temperature of 25±2°C and a dew point of -30°C to -40°C. After 1 hour, the protective film was removed in an argon atmosphere, and the appearance of the lithium ribbon was observed, and the results were recorded in Table 1.
[0052] 2. Cycle performance test
[0053] 1. Battery preparation
[0054] The following assembly is performed under argon atmosphere at an ambient temperature of 25±2°C:
[0055] The lithium metal strips with lithium metal protective layers prepared in Examples 1 to 3 were used as counter electrodes (cut into 15 mm diameter discs), and the lithium iron phosphate pole pieces were used as working electrodes (lithium iron phosphate single-sided coating thickness was 10 mg / cm 2, cut into 12mm diameter discs after rolling), directly stack the counter electrode and the working electrode, assemble and buckle the battery without using a diaphragm; add 2-3 drops of electrolyte, the electrolyte used is a solution containing solvent ethylene carbonate (EC) / dimethyl carbonate (DMC) / ethyl methyl carbonate (EMC) (volume ratio of 1:1:1) and electrolyte 1 mol / L lithium hexafluorophosphate. Three button batteries were made for each.
[0056] The lithium metal strips with lithium metal protective layers prepared in Example 4 and Example 5 and the lithium strips without protective layers prepared in Comparative Example 1 were used as counter electrodes (cut into 15 mm diameter discs), a 15 μm thick polypropylene diaphragm was cut into 16 mm diameter discs as battery diaphragms, and a lithium iron phosphate pole piece was used as a working electrode (lithium iron phosphate single-sided coating thickness was 10 mg / cm 2 , cut into 12mm diameter discs after rolling), three stacked sheets were assembled into button batteries; 2-3 drops of electrolyte were added, the electrolyte used was a solution containing solvent ethylene carbonate (EC) / dimethyl carbonate (DMC) / ethyl methyl carbonate (EMC) (volume ratio of 1:1:1) and electrolyte 1 mol / L lithium hexafluorophosphate. Three button batteries were made in each case.
[0057] 2. Test the battery capacity retention rate after 300 cycles of charge and discharge
[0058] The battery prepared above was subjected to a cyclic charge-discharge test at 25±2°C, with a charge / discharge current density of 0.3 mA / cm 2 , the cut-off charge and discharge voltage range is 3.8~2.0 V, the results are recorded and the capacity retention rate after 300 cycles is calculated. The results are shown in Table 1.
[0059] Table 1
[0060] Examples Battery capacity retention rate after 300 cycles of charge and discharge Appearance of lithium belt after protection performance test Example 1 The average retention rate of the three batteries is 83.2%, and none of them are short-circuited. Maintain metallic luster Example 2 The average retention rate of the three batteries is 84.3%, and none of them are short-circuited. Maintain metallic luster Example 3 The average retention rate of the three batteries is 85.2%, and none of them are short-circuited. Maintain metallic luster Example 4 The average retention rate of the three batteries is 83.6%, and none of them are short-circuited. Maintain metallic luster Example 5 The average retention rate of the three batteries is 84.4%, and none of them are short-circuited. Maintain metallic luster Comparative Example 1 Three are powered off, two of them are short-circuited, and the remaining one has a retention rate of 75.5% Loss of metallic luster → black → grayish white
[0061] From the results in Table 1, it can be seen that after the protective layer is constructed on the surface of the metal lithium strip using the method of the present invention, after it is placed in an environment with a temperature of 25±2℃ and a dew point of -30℃ to -40℃, the oxygen and water in the air have little effect on it, and the original metallic luster is basically maintained; while under the same conditions, the lithium strip without the protective layer of the present invention is gradually corroded, loses its metallic luster and turns black and then white. It can be seen that the protective layer of lithium metal constructed by the present invention can effectively protect lithium metal from contact with air and water.
[0062] It can also be seen from the results in Table 1 that the button cell made of the metal lithium strip with the protective layer constructed by the method of the present invention has a high capacity retention rate and no short circuit occurs after 300 cycles of charge and discharge; while the button cell made of the original lithium strip without the protective layer constructed by the method of the present invention has a low cycle performance and two of the three batteries have short circuits. It can be seen that the protective layer constructed by the method of the present invention can improve the capacity retention rate of the battery, and can also slow down the increase in the linear length of lithium dendrites, thereby improving the safety performance of the battery.
[0063] Since the protective layer of lithium metal of the present invention is flexible, the construction of the protective layer of lithium metal of the present invention can be combined with a lithium belt production line. Before the lithium belt is rolled, a dipping or spraying process of a porous polymer film is added, and then it can be compositely wound with the lithium belt, which is convenient for production.
[0064] It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described above can be combined with each other as long as they do not conflict with each other. In addition, the above are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention.
Claims
1. A protective layer for a rolled metal lithium strip, characterized in that: The invention comprises a hydrophobic porous polymer coating bonded to a metal lithium strip, wherein the hydrophobic porous polymer coating is a hydrophobic porous polypropylene layer, and the holes and bonding surface of the hydrophobic porous polymer coating have perfluoropolyether oil; the perfluoropolyether oil is CF3CF2CF2O(CF2CF2CF2O)mCF2CF3, CF3CF2CF2O(CF(CF3)CF2O) m At least one of CF(CF3)COF, CF3O ((CF2)3O)m(CF2O)nCF3 and CF3O (CF2CF2O)m(CF2O)nCF3, having a number average molecular weight of 1000 to 3000; The protective layer of the rolled metal lithium strip is made by the following method: Step 1, adding a mixture of a polymer, a good solvent and a poor solvent of the polymer in a volume ratio of 10:1 to 5 into a container and stirring until a homogeneous solution is formed, and applying the mixture on the surface of a flat substrate; standing at 10 to 40°C for 3 to 12 hours under a vacuum degree of ≤-90 kPa; drying at 20 to 25°C under normal pressure to form a film, placing the film in a vacuum drying oven at 60 to 80°C and drying for 22 to 25 hours to obtain porous polypropylene-coated polytetrafluoroethylene; peeling to obtain a hydrophobic porous polymer film; wherein the polymer is isotactic polypropylene, and its number average molecular weight is 200,000 to 300,000; Step 2, coating the surface of the hydrophobic porous polymer film with perfluoropolyether oil, and then laminating the coated surface on the surface of a lithium strip to be rolled.
2. The protective layer of the rolled metal lithium strip according to claim 1, characterized in that: The thickness of the hydrophobic porous polypropylene layer is 0.5-30 μm.
3. The protective layer of the rolled metal lithium strip according to claim 2, characterized in that: The thickness of the hydrophobic porous polypropylene layer is 10 to 20 μm.
4. The method for constructing a protective layer of a rolled metal lithium strip according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1: Add a polymer, a good solvent and a poor solvent of the polymer in a volume ratio of 10:1 to 5 into a container and stir until a homogeneous solution is formed, and apply the solution on a flat surface of a substrate; let it stand at 10 to 40°C for 3 to 12 hours under a vacuum degree of ≤-90 kPa; dry it at 20 to 25°C under normal pressure to form a film, put it in a vacuum drying oven at 60 to 80°C and dry it for 22 to 25 hours to obtain a porous polypropylene-coated polytetrafluoroethylene; peel it off to obtain a hydrophobic porous polymer film; Step 2: After coating the surface of the hydrophobic porous polymer film with perfluoropolyether oil, the coated surface is attached to the surface of the lithium strip to be rolled.
5. The method for constructing a protective layer of a rolled metal lithium strip according to claim 4, characterized in that: The good solvent is at least one of xylene, toluene, benzene and decalin; the poor solvent is at least one of butanone, ethanol, methanol, n-butanol and n-propanol.
6. The method for constructing a protective layer of a rolled metal lithium strip according to claim 4 or 5, characterized in that: The coating in step 2 is performed by dipping, brushing or spraying.
7. A rolled metal lithium strip, characterized in that: A protective layer comprising a rolled metal lithium strip according to any one of claims 1 to 3.
8. Use of the rolled metal lithium ribbon as claimed in claim 7 as a negative electrode of a lithium battery.
Citation Information
Patent Citations
Waterproof, air-isolating and dendrite-inhibiting all-solid-state lithium metal protective film and construction strategy thereof
CN114204102A
Method for preparing composite polypropylene microporous film by phase conversion method and product and application of composite polypropylene microporous film
CN110350131A
Lithium metal anode for lithium battery
US20040072066A1